Large genetic divergence of new, morphologically similar species of sterile lichens from Europe (Lepraria, Stereocaulaceae, Ascomycota): concordance of DNA sequence data with secondary metabolites - Fehrer, Judith; Slavíková-Bayerová, Štěpánka; Orange, Alan (Cladistics, 2008)
Lichenized fungi of the genus Lepraria are known for their paucity of morphological characters. Species identification is therefore largely based on secondary chemistry. We investigated different chemotypes of the morphologically highly similar L. jackii species complex by internal transcribed spacer (ITS) sequencing. In phylogenetic analyses including all available Lepraria species, samples belonging to different chemotypes of the L. jackii agg. corresponded to four highly divergent clusters. While true L. jackii was genetically uniform, the other three clades represented previously unrecognized species. They originated from different major speciation events, and two of them were not closely related to any other species. Assessment of intraspecific genetic variability revealed four different patterns with respect to geographic scale. ITS sequences proved to be the most reliable and distinctive characters for species recognition in the Lepraria jackii complex and were in accordance with chemical and ecogeographic data. Frequent occurrence of long branches, relatively few resolved relationships despite high genetic variability, and the discovery and description of a considerable part of the Lepraria species within the last 10 years suggest that the genus is probably much larger than currently known. The diversification of this asexual group in the potential absence of recombination is discussed. © The Willi Hennig Society 2008.